2013
DOI: 10.1161/jaha.113.000212
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Hypomethylation, Ambient Particulate Matter, and Increased Blood Pressure: Findings From Controlled Human Exposure Experiments

Abstract: BackgroundShort‐term exposures to fine (<2.5 μm aerodynamic diameter) ambient particulate‐matter (PM) have been related with increased blood pressure (BP) in controlled‐human exposure and community‐based studies. However, whether coarse (2.5 to 10 μm) PM exposure increases BP is uncertain. Recent observational studies have linked PM exposures with blood DNA hypomethylation, an epigenetic alteration that activates inflammatory and vascular responses. No experimental evidence is available to confirm those observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(165 citation statements)
references
References 44 publications
8
153
3
1
Order By: Relevance
“…A controlled human exposure experiment observed hypomethylation of Alu and the toll-like receptor 4 (TLR4) gene among 15 healthy adults exposed to fine concentrated ambient particles (CAPs) for 130 min. 13 Recently, a longitudinal study reported a relationship between decreased methylation at 3 CpG loci located in the nitric oxide synthase 2, inducible (NOS2A) gene and short-term exposures to organic carbon, elemental carbon, NO 3 ¡ , and NH 4 C among 28 patients with chronic obstructive pulmonary disease. 7 A more recent epigenome-wide study by Panni et al on short-and mid-term PM 2.5 exposure among 3 independent cohorts-the US NAS cohort and the German KORA F3 and F4 cohorts-identified 12 CpG sites at a Bonferroni adjusted significance level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A controlled human exposure experiment observed hypomethylation of Alu and the toll-like receptor 4 (TLR4) gene among 15 healthy adults exposed to fine concentrated ambient particles (CAPs) for 130 min. 13 Recently, a longitudinal study reported a relationship between decreased methylation at 3 CpG loci located in the nitric oxide synthase 2, inducible (NOS2A) gene and short-term exposures to organic carbon, elemental carbon, NO 3 ¡ , and NH 4 C among 28 patients with chronic obstructive pulmonary disease. 7 A more recent epigenome-wide study by Panni et al on short-and mid-term PM 2.5 exposure among 3 independent cohorts-the US NAS cohort and the German KORA F3 and F4 cohorts-identified 12 CpG sites at a Bonferroni adjusted significance level.…”
Section: Discussionmentioning
confidence: 99%
“…The literature to date indicates that DNA methylation may be an important pathway linking particulate matter (PM) to health outcomes. [6][7][8][9][10] For example, changes in patterns of DNA methylation may be associated with processes leading to cardiovascular diseases.. 11,12 There is growing evidence that exposure to PM is associated with global DNA methylation and gene-specific methylation, 6,7,13,14 especially for exposure to metal-rich PM in occupational settings. 15, 16 Yet, little is known regarding how PM exposure affects DNA methylation on a genome-wide level.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported PM 2.5 -related reductions in DNA methylation in noncoding repetitive elements, including long interspersed nuclear element-1 (20) and Alu (21), a short interspersed nuclear element, both of which are considered surrogates for global methylation. However, few epidemiologic studies have investigated the associations between PM 2.5 and short-term changes in methylation at specific sites in the DNA, where a cytosine nucleotide is followed by a guanine nucleotide in the sequence of bases along the 5′ to 3′ direction and the nucleotides are separated by 1 phosphate (cytosine-phosphate-guanine (CpG)), that regulate inflammation responses (19,(21)(22)(23)(24). In addition, most epidemiologic studies have relied on outdoor, fixed air-quality monitoring stations, which poorly approximate individual exposures, which in turn depend on patterns of daily activity and microenvironments (25,26).…”
mentioning
confidence: 99%
“…t (for β 1 ) = 5.253 t (for β 2 ) = 3.090 The value of t n-k-1, α / 2 = 2.26 Here t > t n -k -1; α /2 ; therefore reject H 0 . Hence, β1≠ 0 and β 2 Analysis indicates that increase in has positive correlation with exposure duration and exposure concentration of RSPM. It indicates that two independent variables Exposure Duration and Particulate Concentration jointly account for the variation in ISBP upto 80.5% and remaining 19.5 % variation is due to other reasons.…”
Section: Methodology and Observationsmentioning
confidence: 96%
“…Singh et al, (2007), assessed the reduction in forced vital capacity of lungs of sand stone quarry workers exposed to high respirable suspended particulate concentration. He found that exposure duration and exposure concentrations are main factors responsible to damage respiratory tract of worker [4].According to Bellavia et al, (2013), Short-term exposures to fine (<2.5 lm aerodynamic diameter) ambient particulate-matter (PM) have been related with increased blood pressure (BP) in controlled-human exposure and community-based studies [2]. Kumar et al, (2014), performed pulmonary function test on quarry workers and control population and found that reduction of pulmonary function values were positively correlated with duration of their work.…”
Section: Imentioning
confidence: 99%